Teaching Conceptions of Inquiry-based Learning among Nigerian Secondary School Physics Teachers - Bako, Aliyu; Aliah Phang, Fatin (International Journal of Psychosocial Rehabilitation, 2020)
Inquiry-based learning (IBL) is gaining popularity in science education worldwide. Unfortunately, many teachers are yet to comprehend its pedagogical modus operandi, especially in West Africa and Nigeria, in particular, maybe due to their teaching conception that is still inclined towards a teacher-centered paradigm. This paper is targeted at finding out the teachers’ teaching conception towards IBL in secondary schools in Kebbi State, Nigeria. The Promoting Inquiry-Based Learning in Science and Mathematics (PRIMAS) questionnaire was administered to a sample of 85 physics secondary school teachers in Kebbi State. Descriptive statistics was used to arrive at a mean value of 2.74, which represents the value of the physics teachers conception. Inadequate knowledge of IBL, teachers’ difficulty in applying the method, and current practices (national curriculum and lack of adequate instructional materials) were found to be some of the respondents’ major conceptions. Professional development programs, curriculum review, and IBL teachers’ welfare were some of the suggestions offered to improve the teaching conception towards IBL.